Pelatihan Pengelolaan Sampah Domestik melalui Pengukuran Timbulan Sampah di Desa Sakerta Timur, Darma, Kuningan - Nurdin, Nurdin; Yudhayana, Bambang; Karyaningsih, Ika; Mulyanto, Age; Fatah, Eep Saeful; Rahardian, Haydar (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2023)
The potential for the generation of organic and inorganic waste is increasing in line with the increase in population and lifestyle. Domestic waste generation data were obtained based on a family survey by sampling. For 8 (eight days). The data were analyzed according to the Indonesian National Standard (SNI) 19-3964-1994. The results obtained show that the amount of inorganic waste is greater than organic waste. This potential can be utilized as a business activity unit for BUMDESA by establishing 3R TPS. The community paradigm changes after assessing the economic potential of organic and inorganic waste generation.